The similarity of Malay architecture terminology: perahu and house / Mohamad Hanif Abdul Wahab and Azizi Bahauddin - Abdul Wahab, Mohamad Hanif; Bahauddin, Azizi (UiTM Press, 2017)
The perahu also known as boat was used by the Malay community during the Holocene period when the rise of the sea level altered the Malay world and it became islands and a peninsula. The perahu became important, not only as a navigational vessel but served as a shelter during the journey. As sailing is a part of Malay way of life, many perahu manifestations are often seen in housing construction. The objectives of this paper are to outline the features of perahu used around Negeri Sembilan traditional house – architecture with kajang perahu analogy – and to raise questions on what are the similarities between the terminology perahu and house. The questions look through literature review analysis and identify elements and components related to the house.